2012
DOI: 10.1097/prs.0b013e31826d1682
|View full text |Cite
|
Sign up to set email alerts
|

Donor-Site Lymphatic Function after Microvascular Lymph Node Transfer

Abstract: Therapeutic, IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
91
0
5

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(98 citation statements)
references
References 26 publications
2
91
0
5
Order By: Relevance
“…25,26 In contrast, the connections between lymphatics and nearby veins in LVA procedures typically are superficial and require only a fraction of the lymphatics in the affected limb. In this series, we opted for VLNT over LVA in patients with upper extremity lymphedema because we believed that the risk of donor site lymphedema may be lower when harvesting from the groin compared with the axilla or chest wall.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 In contrast, the connections between lymphatics and nearby veins in LVA procedures typically are superficial and require only a fraction of the lymphatics in the affected limb. In this series, we opted for VLNT over LVA in patients with upper extremity lymphedema because we believed that the risk of donor site lymphedema may be lower when harvesting from the groin compared with the axilla or chest wall.…”
Section: Discussionmentioning
confidence: 99%
“…However, one study reported a small change in the postoperative lymphoscintigraphies in donor site legs, and another study described new-onset lymphedema in donor limbs. 40,41 Intraoperative laser imaging of lymph nodes with indocyanine green dye can guide selective VLNT lymph node collection. Sentinel lymph node mapping of donor sites with technetium tracer and the collection of lymph nodes other than the sentinel nodes can further improve safety (Fig.…”
Section: Vascularized Lymph Node Transfer (Vlnt)mentioning
confidence: 99%
“…The superficial inguinal lymph nodes are fed by the SCIA, SIEA, and the medial artery [4]. Recent studies have shown that nodes in the inferior-medial and the central areas of the saphenofemoral junction should not be selected as donor sites for VLNT, because they are the primary superficial nodes draining the lower limb [2,3]. Nodes in the superior area of the saphenofemoral junction are said to be safe, but they can be the draining nodes for the lower limb in 15% of the cases [3].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that nodes in the inferior-medial and the central areas of the saphenofemoral junction should not be selected as donor sites for VLNT, because they are the primary superficial nodes draining the lower limb [2,3]. Nodes in the superior area of the saphenofemoral junction are said to be safe, but they can be the draining nodes for the lower limb in 15% of the cases [3]. Scaglioni et al [5] showed that the superficial inguinal lymph nodes could be divided into three subgroups: abdominal, medial thigh, and lateral thigh nodes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation